Imperativeness in between Grammatical Givens and Communicative Politeness - Palašić, Nikolina; Zbašnik, Tihana (Poznańskie Studia Slawistyczne, 2017)
The paper focuses on the relation between imperatives and imperativeness, that is, between the imperative as a grammatical mood with a defined form and its assigned function, on the one hand, and imperativeness as a communicative value that can manifest itself through different morphosyntactic forms, on the other. In this sense, the function of imperatives is analysed in the context of the theory of speech acts. The analysis reveals that different imperative forms can be classified as different types of speech acts based on their various communicative roles. The theory of politeness dictates that directness, which is a basic feature of imperatives, should be avoided in polite communication. This is why we also focus on other morphosyntactic forms whose form indicates a reduced level of directness, but whose content still has the characteristics of imperatives.